Cold Cracking Technology for Crude Oil Upgrading in Qaiyarah Heavy Oil Field; Technical and Economical Evaluation - Bibani, Herish; A. Alhaleem, Ayad; Sharifi, Mohammad (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Heavy oil is classified as unconventional oil resource because of its difficulty to recover in its natural state, difficulties in transport and difficulties in marketing it. Upgrading solution to the heavy oil has positive impact technically and economically specially when it will be a competitive with conventional oils from the marketing prospective. Developing Qaiyarah heavy oil field was neglected in the last five decades, the main reason was due to the low quality of the crude oil resulted in the high viscosity and density of the crude oil in the field which was and still a major challenge putting them on the major stream line of production in Iraq. The low quality of the crude properties led to lower oil prices in the global markets as well as the high operation cost of production and transportation. The purpose of this paper is testing new technology applications on an Iraqi Heavy Oil Field and specifically (Qaiyarah Oil Field) by applying the cold cracking technique to upgrade Qaiyarah heavy oil properties through using series of electrical/ mechanical activities applied on the heavy crude that generates special kind of vibrations to re-structure the (H-C) bonds in the heavy oil to convert it to lighter crude with lower viscosity/ density which was the outcome of the distillation by reducing the unsaturated components and isolating the minerals and sulfur as sold components. The results were very optimistic, where the density has improved from 16 to 30.5 API degree, sulfur content has reduced from 6.4 to 1.507 weight percent and selling price per barrel would increase by 53% compare to 2.31% cost increment due to the upgrading operation. Therefore, applying the cold cracking technology is convenience for improving Qaiyarah oil properties as the main production stream line will be increased in Iraq.